Case studies to enhance student evaluation : 2015 Bond University : engaging students in feedback through executive leadership. - Kinash, Shelley; Naidu, Vishen; Santhanam, Elizabeth; Fleming, Julie; Tulloch, Marian; Tucker, Beatrice; Sid Nair, Chenicheri; Judd, Madelaine-Marie; Fleming, M. (Office for Learning and Teaching, 2015)
Online student evaluation systems are an opportunity for student engagement and learning improvement. However, they are currently limited by low response rates. Educators tend not to trust them and students describe the activity of filling in multiple surveys as futile. Student feedback processes have largely become academic performance review instruments rather than evaluation and change catalysts. However, there are universities successfully using student evaluation to measure student course engagement and learning development, and then involving students in improving the overall student experience. This document presents a case study from a project designed to fully develop at least six such innovations into case studies. The project pursued the questions: how can we measure student engagement and learning success using student evaluation processes? And how can students contribute to on-going improvement in university learning and teaching? The team drew out a cohesive set of key issues, strategies and recommendations to disseminate to the higher education sector through a symposium. This paper reports what Bond University did to resolve the four problems of: response rates; student comments; question content; and application to reported quality improvement.